Implementasi Fuzzy Mamdani Menentukan Tingkat Kepuasan Penumpang Trans Metro Deli Kota Medan - Aruan, Nur Jamilah; Hasugian, Abdul Halim (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Medan City is one of the major cities in Indonesia with a dense population. To meet the transportation needs of the population, the Medan City government launched Trans Metro Deli, a convenient and efficient public transportation service. However, in recent times, the Trans Metro Deli bus has experienced a significant decline in passenger numbers. Therefore, the bus transport management needs to do the right strategy to retain their customers. To overcome this problem, this study aims to evaluate and analyze the level of satisfaction of Trans Metro Deli passengers using fuzzy methods. The Mamdani fuzzy method was chosen because it has a flexible tolerance and the results are more in line with human perception. Through the use of questionnaires, passengers' opinions and expectations are evaluated and calculated using the fuzzy method. Previous research using similar methods has provided effective results in determining passenger satisfaction levels in other sectors. The variables used in this study are facilities, price, service quality, and location. The data was collected from a one-month field study. The Mamdani fuzzy process involves four stages, namely fuzzyfication, inference, rule composition, and defuzzyfication. These stages are used to convert input values into fuzzy outputs that represent the membership level of each variable. The result obtained is 74.4. The results of this study are expected to provide recommendations for improving service quality on Trans Metro Deli buses. Thus, transportation managers can meet passenger expectations and retain their consumers. Through the implementation of Mamdani fuzzy, it is expected to achieve an increase in the satisfaction of Trans Metro Deli passengers in Medan City.